Have mysterious topological valley currents been observed in graphene superlattices?. (7th January 2022) - Roche, Stephan; Power, Stephen R; Nikolić, Branislav K; García, José Hugo; Jauho, Antti-Pekka
Abstract: We provide a critical discussion concerning the claim of topological valley currents, driven by a global Berry curvature and valley Hall effect proposed in recent literature. After pointing out a major inconsistency of the theoretical scenario proposed to interpret giant nonlocal resistance, we discuss various possible alternative explanations and open directions of research to solve the mystery of nonlocal transport in graphene superlattices.